Hepatosteatosis: 100 cases - İbrahim Halil BAHÇECİOĞLU,; Hakan ŞENTÜRK,; Ali MERT,; Gürkan BAŞARAN,; Mesut AKÇAKAYA,; İbrahim KELEŞ,; Fehmi TABAK,; Mahmut İLHAN,; Perihan AKIN,; Gülşen ÖZBAY, (Turkish Journal of Gastroenterology, 2019)
-